The Influence of Financial Performance on Stock Price with Exchange Rate as Moderation Variable - Badriyah, Lailatul; Z. A, Zahroh; Darmawan, Ari (FIA UB, 2025)
With the exchange rate acting as a moderating variable, this study aims to examine the effect of Return on Equity (ROE), Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Earnings per Share (EPS) on stock prices in consumer goods subsector manufacturing companies listed on the Indonesia Stock Exchange between 2017 and 2022. Using SPSS version 25.0.0, the analysis techniques used are multiple linear and moderated regression analyses (MRA). The research findings show that before and during the COVID-19 epidemic, stock prices were significantly influenced by ROA, ROE, CR, DER, and EPS. According to the MRA results, the exchange rate can also strengthen the impact of ROA, ROE, DER, and EPS on stock prices in both eras. However, before and during the epidemic, the exchange rate does not reduce the impact of CR on stock prices. When making financial plans and investment decisions in the face of economic uncertainty, investors and business managers can benefit significantly from these findings.